Amyloidosis: disease caused by amyloid - Pepys, Mark (Henry Stewart Talks, 2007)
What is, and what is not amyloidosis, Amyloid deposits, Clinical amyloidosis, Amyloid fibrillogenesis, Tissue damage by amyloid, Imaging amyloid in vivo, Treatment of amyloidosis
Archived at 2016/04/17